Obliteration of Intercondylar Notch Mimicking Flexion-Extension Gap Imbalance in a Cruciate Retaining Total Knee Arthroplasty - Harun Resit Gungor; Esat Kiter; Semih Akkaya; Nusret Ok; Cagdas Yorukoglu (Case Reports in Orthopedics)
Following total knee arthroplasty (TKA), the most frequent cause of extension deficit and limitation of range of motion in early postoperative period is related to improper tensioning of soft tissues and failure to balance extension and flexion gaps. If a cruciate retaining (CR) prosthesis is the planned implant, then attention should be given to balancing the posterior cruciate ligament (PCL), and any factor that alters this balance may also cause deterioration of knee balance in postoperative period. Here, we report on an unusual case referred from another hospital because of continuous pain and restriction of knee motion in early postoperative period following CR-designed TKA that was initially thought to be due to flexion-extension imbalance. However, during the revision procedure, extruded cement to the intercondylar notch was found to be both mechanically blocking terminal extension and limiting flexion by possible mechanism of irritation of the synovial nerve endings around the stretched anterior fibers of PCL during flexion. This case was successfully treated by removal of extruded cement from intercondylar notch to decompress PCL, polyethylene exchange, and secondary patellar resurfacing.